2012
DOI: 10.3109/10837450.2012.693505
|View full text |Cite
|
Sign up to set email alerts
|

Oral transmucosal delivery of domperidone from immediate release films produced via hot-melt extrusion technology

Abstract: The objective of the study was to prepare and characterize the domperidone (DOM) hot-melt extruded (HME) buccal films by both in vitro and in vivo techniques. The HME film formulations contained PEO N10 and/or its combination with HPMC E5 LV or Eudragit RL100 as polymeric carriers, and PEG3350 as a plasticizer. The blends were co-processed at a screw speed of 50 rpm with the barrel temperatures ranging from 120-160°C utilizing a bench top co-rotating twin-screw hot-melt extruder using a transverse-slit die. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Subsequently the mixture is cast onto a substrate surface and the solvent is allowed to evaporate, leading to the formation of a drug-containing polymeric film. Alternatively, hotmelt extrusion is another method to prepare an oral film [104][105][106][107]. It has the advantage of avoiding the use of organic solvent but is not suitable for thermo-labile compounds [108].…”
Section: Oral Films and Wafersmentioning
confidence: 99%
“…Subsequently the mixture is cast onto a substrate surface and the solvent is allowed to evaporate, leading to the formation of a drug-containing polymeric film. Alternatively, hotmelt extrusion is another method to prepare an oral film [104][105][106][107]. It has the advantage of avoiding the use of organic solvent but is not suitable for thermo-labile compounds [108].…”
Section: Oral Films and Wafersmentioning
confidence: 99%
“…Hot melt extrusion (HME) offers the advantage of a solvent-free process for ODF manufacturing (Palem et al, 2016(Palem et al, , 2013Park et al, 2015;Repka et al, 2003). Yet, poor availability of suitable polymers and high temperatures may pose stability issues to the active (Hoffmann et al, 2011).…”
Section: Manufacturing Technologiesmentioning
confidence: 99%
“…However, few researchers have demonstrated that HME techniques are a viable method to prepare novel, scalable delivery systems via extruded films. Indeed, very few oral transmucosal systems are currently available in the market [18]. …”
Section: Introductionmentioning
confidence: 99%